INNOVATION OF EDUCATION MANAGEMENT STRATEGIES TO IMPROVE THE QUALITY OF LEARNING IN MADRASAH EDUCATIONAL INSTITUTIONS - Mabrur, Ali; Mubarak, A Faizul (PROCEEDING OF INTERNATIONAL CONFERENCE ON EDUCATION, SOCIETY AND HUMANITY, 2024)
This research aims to analyze and evaluate educational management strategies applied in MI Miftahul ulum village deep Gading with a focus on improving the quality of learning. Through a qualitative and quantitative approach, the study explores the various strategies that have been implemented by the institutions to improve the effectiveness and efficiency of the learning process. This research uses methods of qualitative analysis of descriptive research. With a collation of research at MI Miftahul ulum village deep deep Gading. Data analysis using data collection methods through interviews, class observations, and document analysis related to educational management strategies that have been implemented. The research identified several key strategies, including the use of technology in the learning process, the involvement of parents in supporting the education of their children, the implementation of innovative learning models, and improved teacher training and development. In addition, the study also assessed the positive impact of such strategies on student academic achievement, learning motivation, and active participation in extracurricular activities.